In defence of the standard psychological theory: can a person be a type? - A. V. Mertsalov (Омский научный вестник: Серия "Общество. История. Современность")
The paper presents a defense of the standard psychological theory of personal identity against Mark Walker’s criticism of it. Walker claims that the conceptual tools of standard psychological theory of personal identity are insufficient to solve the problematic cases of branching in the context of moral and legal responsibility questions, and argues in favor of an approach to these problems that involves the type/token distinction. In the current paper I argue against Walker that the approach he suggests is untenable, and that the conceptual tools of standard psychological theory are sufficient to provide an adequate analysis of the cases mentioned.